Sosialisasi dan Edukasi Kepada Masyarakat Mengenai Pencegahan Penyebaran Covid 19 Pada Jaringan Lunak : Sosialisasi dan Edukasi Kepada Masyarakat Mengenai Pencegahan Penyebaran Covid 19 - Ahmad Firman; Dirwan; Muhammad Fachrul Sjarlis; Andi Ummul Khaer (ADPERTISI, 2023)
The presence of the Covid-19 pandemic has brought changes to the world with various challenges that were never imagined before. Stopping the spread of this virus is not enough just to prevent its transmission from oneself, but also must be assisted from various aspects of the role, starting from the government, other professions to the community itself. For this reason, it is important to conduct educational socialization regarding preventing the spread of Covid 19 in soft tissue. This community service activity is carried out with socialization and education activities on how to prevent and handle the spread of Covid-19 in soft tissue in the community in Tamangapa Village, Manggala District, Makassar City. After this socialization and education was carried out, preventive measures against Covid-19 began to be implemented by the community. The community is aware of the application and habituation of healthy living behaviors such as maintaining cleanliness, discipline in wearing masks, diligently washing hands with soap and clean water, providing hand sanitizers and disinfectants at home and public places, maintaining distance and reducing activities outside the home as an effort to terminate chain of spread of Covid-19. In addition, after this socialization, the community already knows how to provide basic aid for soft tissue injuries.